Interleukin-8 Secreted by Glioblastoma Cells Induces Microvascular Hyperpermeability Through NO Signaling Involving S-Nitrosylation of VE-Cadherin and p120 in Endothelial Cells - Guequén, Anita; Zamorano, Patricia; Córdova, Francisco; Koning, Tania; Torres, Angelo; Ehrenfeld, Pamela; Boric, Mauricio P.; Salazar-Onfray, Flavio; Gavard, Julie; Durán, Walter N.; Quezada, Claudia; Sarmiento, José; et al. (Frontiers in Physiology, 2019)
Glioblastoma is a highly aggressive brain tumor, characterized by the formation of dysfunctional blood vessels and a permeable endothelial barrier. S-nitrosylation, a posttranslational modification, has been identified as a regulator of endothelial function. In this work we explored whether S-nitrosylation induced by glioblastoma tumors regulates the endothelial function. As proof of concept, we observed that S-nitrosylation is present in the tumoral microenvironment of glioblastoma in two different animal models. Subsequently, we measured S nitrosylation and microvascular permeability in EAhy296 endothelial cells and in cremaster muscle. In vitro, conditioned medium from the human glioblastoma cell line U87 activates eNOS, causes VE-cadherin- S-nitrosylation and induces hyperpermeability. Blocking Interleukin-8 (IL-8) in the conditioned medium inhibited S-nitrosylation of VE-cadherin and hyperpermeability. Recombinant IL-8 increased endothelial permeability by activating eNOS, S-nitrosylation of VE-cadherin and p120, internalization of VE-cadherin and disassembly of adherens junctions. In vivo, IL-8 induced S-nitrosylation of VE-cadherin and p120 and conditioned medium from U87 cells caused hyperpermeability in the mouse cremaster muscle. We conclude that eNOS signaling induced by glioma cells-secreted IL-8 regulates endothelial barrier function in the context of glioblastoma involving S-nitrosylation of VE-cadherin and p120. Our results suggest that inhibiting S-nitrosylation may be an effective way to control and/or block damage to the endothelial barrier and prevent cancer progression.